Apical Microleakage in Root Canals Obturated With 2 Different Endodontic Sealer Systems in Canine Teeth of Dogs. (June 2017) - Lothamer, Chad W.; Anderson, Ashley; Hetzel, Scott J; Adrian, Alex I.; Snyder, Christopher; Goldschmidt, Stephanie; Soukup, Jason W.
An apical dye leakage test was utilized to compare 2 endodontic sealer systems commonly used in veterinary endodontic treatment. Rotary instrumentation followed by injection of 2 different sealers (GuttaFlow 2 and AH Plus) and a single master cone obturation technique were compared. Following obturation and restoration, specimens were immersed in India ink for 48 hours. A tooth mineral clearing technique was utilized to render the tooth samples transparent. Subsequently, the apices were evaluated for prevalence and magnitude of apical dye penetration under magnification. Statistical analysis of the results revealed no significant differences in the prevalence or magnitude of apical dye penetration between groups.